Clinicoepidemiological Profile of Short Stature at a Tertiary Care Centre in North India - Rajan, Mahima; Vaswani, Narain Das; Lekhwani, Seema; Bansal, Mohit (Indian Journal of Child Health, 2020)
Background: Short stature (SS) is a common pediatric problem. The goal of the evaluation of a child with SS is to identify the subset of children with pathologic causes so that appropriate timely intervention can be made. Aim: The aim of the study was to study the clinical, epidemiological, and etiological profile of SS at a tertiary hospital of north India. Materials and Methods: This was an observational analytical study and was conducted in the department of pediatrics, over a period of 1 year (October 2016– September 2017). A total of 100 children aged 3–14 years, with height